Analysis of Trouble Ticket Documents in the Srikandi 3 Application for Archives Management at the Ministry of Health - Evi Zakiyah; Al Muhdil Karim (International Journal of Science and Environment (IJSE), 2025)
Records management is a crucial component of contemporary information governance, particularly for government agencies responsible for the storage, preservation, and accessibility of daily operational documents. The SRIKANDI application has been adopted by various agencies in Indonesia, at both the central and regional levels, and offers significant technical and managerial benefits to the Ministry of Health. This study employs a qualitative approach based on a literature review and analysis of the Problem Inventory List (DIM) Letters sent by the Ministry of Health to archives authorities. The analysis shows that the system's trouble ticket tracking mechanism enables a structured, continuous improvement process, with the entire handling cycle—from ticket creation, allocation, follow-up, and closure—systematically documented. Furthermore, the advanced reporting functionality of the ticket platform allows quantitative monitoring of the number of incoming tickets, average resolution time, and Service Level Agreement (SLA) violations, thereby enhancing transparency, accountability, and effectiveness of records management within the government. These findings recommend the integration of monitoring into key managerial policies.